Biodiversity loss underlies the dilution effect of biodiversity. (18th August 2020) - Halliday, Fletcher W.; Rohr, Jason R.; Laine, Anna‐Liisa
Abstract: The dilution effect predicts increasing biodiversity to reduce the risk of infection, but the generality of this effect remains unresolved. Because biodiversity loss generates predictable changes in host community competence, we hypothesised that biodiversity loss might drive the dilution effect. We tested this hypothesis by reanalysing four previously published meta‐analyses that came to contradictory conclusions regarding generality of the dilution effect. In the context of biodiversity loss, our analyses revealed a unifying pattern: dilution effects were inconsistently observed for natural biodiversity gradients, but were commonly observed for biodiversity gradients generated by disturbances causing losses of biodiversity. Incorporating biodiversity loss into tests of generality of the dilution effect further indicated that scale‐dependency may strengthen the dilution effect only when biodiversity gradients are driven by biodiversity loss. Together, these results help to resolve one of the most contentious issues in disease ecology: the generality of the dilution effect. Abstract : The dilution effect predicts increasing biodiversity to reduce the risk of infection, but the generality of this effect remains unresolved. Here, by re‐analyzing the (often conflicting) results of previously published meta‐analyses, we show that ecological processes like habitat fragmentation, urbanisation, and agricultural intensification consistently lead to increases in infectious diseases, likely because these events drive concurrent losses of local biodiversity and predictable changes in host community composition.